Association between Vitamin D Deficiency and Insulin Resistance in Type 2 Diabetic Adult Patients: Systematic Review - Salman Alharbi, Saud; Alfaqiri, Manar Saud A; Alanazi, Najla Khaldun A; Alanazi, Arwa Fraih N; Albaridi, Rand Fahad M; Alquthami, Hatem Hamad M; Aljohani, Riymaz Jameel M; Alqarni, Rana Hasan S; Alnajim, Sarah Talal A; Althobiti, Alaa Mansour F; Albalawi, Ashwaq Awad M; Alqahtani, Mohammed Masoud H; et al. (Saudi Medical Horizons Journal, 2025)
The recognized biomarker of vitamin D status have been repeatedly linked to an increased risk of insulin resistance, metabolic syndrome, and the subsequent development of type 2 diabetes, according to an increasing body of epidemiological evidence. This systematic review aimed to investigate the relationship between vitamin D deficiency and insulin resistance (IR) in adults with Type 2 Diabetes Mellitus (T2DM). It highlights a consistent inverse association between vitamin D levels and IR, but the efficacy of vitamin D supplementation in improving IR remains inconsistent across various interventional studies. The review followed PRISMA guidelines and included a systematic search of studies in multiple databases, yielding 13 studies with 1,396 participants. Most observational studies (8 of 11) showed a significant inverse correlation between serum 25-hydroxyvitamin D and HOMA-IR. However, interventional studies produced conflicting results; one randomized controlled trial (RCT) indicated improvement in HOMA-IR with high-dose vitamin D supplementation, while others found no effect. The overall evidence quality was deemed low, with a high risk of bias attributed to the lack of control for confounders like body mass index (BMI) and physical activity. Despite the consistent reporting of an inverse relationship in observational studies, interventional data do not support a causal link. The inconsistency across studies may reflect confounding by BMI, sunlight exposure, and physical activity. Consequently, current evidence does not strongly advocate for vitamin D supplementation as an isolated treatment for improving insulin resistance in T2DM, underlining the necessity for more rigorous clinical trials.